CRISPR-mediated base editing in mice using cytosine deaminase base editor 4 - Salah Adlat; Farooq Hayel; Ping Yang; Yang Chen; Zin Mar Oo; May Zun Zaw Myint; Rajiv Kumar Sah; Noor Bahadar; Mahmoud Al-Azab; Fatoumata Binta Bah; Yaowu Zheng; Xuechao Feng (Electronic Journal of Biotechnology, 2021)
Background: Many human genetic diseases arise from point mutations. These genetic diseases can theoretically be corrected through gene therapy. However, gene therapy in clinical application is still far from mature. Nearly half of the pathogenic single-nucleotide polymorphisms (SNPs) are caused by G:C>A:T or T:A>C:G base changes and the ideal approaches to correct these mutations are base editing. These CRISPR-Cas9-mediated base editing does not leave any footprint in genome and does not require donor DNA sequences for homologous recombination. These base editing methods have been successfully applied to cultured mammalian cells with high precision and efficiency, but BE4 has not been confirmed in mice. Animal models are important for dissecting pathogenic mechanism of human genetic diseases and testing of base correction efficacy in vivo. Cytidine base editor BE4 is a newly developed version of cytidine base editing system that converts cytidine (C) to uridine (U). Results: In this study, BE4 system was tested in cells to inactivate GFP gene and in mice to introduce single-base substitution that would lead to a stop codon in tyrosinase gene. High percentage albino coat-colored mice were obtained from black coat-colored donor zygotes after pronuclei microinjection. Sequencing results showed that expected base changes were obtained with high precision and efficiency (56.25%). There are no off-targeting events identified in predicted potential off-target sites. Conclusions: Results confirm BE4 system can work in vivo with high precision and efficacy, and has great potentials in clinic to repair human genetic mutations.How to cite: Adlat S, Hayel F, Yang P, et al. CRISPR-mediated base editing in mice using cytosine deaminase base editor 4. Electron J Biotechnol 2021;52. https://doi.org/10.1016/j.ejbt.2021.04.010